(untitled) (World Bulletin of Public Health, 2025)
Heart rhythm disorders, or arrhythmias, refer to irregularities in the heartbeat, which can lead to serious health complications if left untreated. This article provides an in-depth analysis of arrhythmias, their causes, types, diagnostic methods, and treatment approaches. The discussion includes a review of current literature, methodologies for diagnosing and managing arrhythmias, results from recent studies, and potential future directions for research and treatment.